2016
DOI: 10.1093/chromsci/bmw196
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Structure Elucidation of Forced Degradation Products of the Novel Propionic acid Derivative Loxoprofen: Development of Stability-Indicating Chromatographic Methods Validated as per ICH Guidelines

Abstract: Loxoprofen sodium (LOX) is a recently developed novel propionic acid derivative. Owing to its instability under both hydrolytic and oxidative conditions, the development of simple, rapid and sensitive methods for its determination in the presence of its possible forced degradation products becomes essential. Two simple chromatographic methods, high-performance thin layer chromatography (HPTLC) and high-performance liquid chromatography (HPLC), were developed associated with ultraviolet (UV) detection. In HPTLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It is reported that the biological effects of some pharmaceuticals are changed by UV irradiation [6,7,8] on account of their photoconversion to photoproducts. Various photochemical reactions may be induced by UV irradiation [9,10,11]. These reports indicate that the generation of various photoproducts is dependent on these chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the biological effects of some pharmaceuticals are changed by UV irradiation [6,7,8] on account of their photoconversion to photoproducts. Various photochemical reactions may be induced by UV irradiation [9,10,11]. These reports indicate that the generation of various photoproducts is dependent on these chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, additional research showed that the oxidation of the dihydropyridine ring following the generation of pyridine derivatives was the main degradation mechanism [7,13,14]. There are some reports showing the more complex photochemical reaction of nifedipine with the formation of further photoproducts [10,15,16]. Moreover, photoproducts of dihydropyridine have no therapeutic effects [7,8].…”
Section: Introductionmentioning
confidence: 99%